Implementasi Wireless Sensor Network untuk Monitoring Kesuburan Lahan Pertanian Padi menggunakan Modul Wifi ESP8266 - Krisna Wahyu Aji Kusuma; Nurul Hidayat; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Indonesian is a country where a third of its population works from the agricultural sector, especially rice fields. Most farmers expect maximum yields without knowing the soil fertility with the factors that support this fertility. Factors such as soil pH, soil moisture, soil temperature and various other factors. Especially the factors can also change at any time that could interfere with the process of plant growth if farmers do not pay attention to these changes. With the developing technology, we can make it easier to monitor soil pH, soil moisture and soil temperature using the YL-69, DS18B20 and soil pH meter sensors. The data taken by the three sensors will be accommodated in the sensor node and then sent to the gateway via the websocket and forwarded to firebase and then displayed to the web interface. Testing is done using quality of service to determine the performance of the network performance from delivery speed, packet lost during delivery, and time interval of each delivery. Then the performance test results obtained, namely the throughput of H-1 to H-3 is 12.11 bps, 10.88 bps, and 16.13 bps. Packet loss from H-1 to H-3 is 0.4%, 0.3%, and 0.2%. The delay from H-1 to H-3 is 0.12 s, 0.09 s, and 0.09 s. The tool's function test works successfully with data taken from the three sensors that can be displayed on the web interface.